ANALISIS HUBUNGAN TINGKAT PRODUKSI DENGAN TINGKAT PENDAPATAN PETANI RUMPUT LAUT DI DESA PUNAGA KECAMATAN MANGARABOMBANG KABUPATEN TAKALAR - Farhanah Wahyu (Universitas Muhammadiyah Makassar, 2018)
Mangarabombang is one of the locations of seaweed cultivation in Takalar and Punaga is one of village in Mangarabombang who has waters location are very supportive of local government programs to increase national production of seaweed. To Increase of seaweed is based on the government's target in Takalar So, this reaseach aims to determine effect of production levels and income levels, analysis factors that influence the risk level of production and income as well as farmer's behavior in the face of the risk of seaweed production. The method of this reseach are random sampling of respondents with income data analysis, R/C Ratio and correlation of production and income. After processing data, showed that respondents increase seaweed production in 2014 to 2016 has significant change by followed a decrease levels income during 2016. Because of seasons and pricing from government uncertain about the unit price of seaweed in the market. In addition, the correlation data analysis showed that a strong correlation between production of seaweed and income of seaweed farming to continue in future. So much needed attention by government to make strategic policy for the increase production of seaweed and income of farmer to make sustainable seaweed better.